Differences between 1999 and 2010 across the 1 Falkland Plateau: Fronts and water masses - Pérez-hernández, M. Dolores; Hernández-guerra, Alonso; Comas-rodríguez, Isis; Benítez-barrios, Verónica M.; Fraile-nuez, Eugenio; Pelegrí, Josep L.; Naveira Garabato, Alberto C. (SEANOE, 2017)
Data used in the Paper cited. It includes CTD data in .mat format from the Moc-Austral (2010) and ALBATROS (1999) cruises.